Aflatoxin M1 in the urine of non-carriers and chronic carriers of hepatitis B virus in Maringa, Brazil - Marcel Padovani Giolo; Christiane Minervino de Oliveira; Dennis Armando Bertolini; Maria Valdrinez Campana Lonardoni; Matheus Sampaio Gouveia; Daisy Pontes Netto; Suzana Lucy Nixdorf; Miguel Machinski Junior (Universidade de São Paulo, 2012)
Exposure to aflatoxins (AFs) in the diet may favour the development of hepatocellular carcinoma (HCC) and the acute exacerbation of hepatitis in chronic hepatitis B virus (HBV) carriers. Measurement of biomarkers such as aflatoxin M1 (AFM1), a metabolite of aflatoxin B1 (AFB1), in urine allows for the assessment of populations exposed to aflatoxins. The aim of this study was to investigate the occurrence of aflatoxin M1 in the urine of HBV carrier and non-carrier patients. One group included 43 randomly selected HBV carriers treated at two hospitals in the city of Maringa, Brazil, from March to June 2008. Control group consisted of 29 healthy adult volunteers with anti-HBs positive and HBsAg negative test results. Detection of AFM1 was performed by fluorescence using high performance liquid chromatography (HPLC) and post-column derivation with the Kobra Cell®. Of the 72 samples analysed, 05/29 (17.2%) AFM1 positive samples were from HBV non-carriers, and 16/43 (37.2%) of samples were from chronic HBV carriers. This study showed AFM1 in the urine of the two surveyed population. However, there is evidence that the chronic HBV carriers have a higher risk of developing HCC due to additive interaction between AFs and HBV. A exposição às aflatoxinas (AFs) na dieta é um fator de risco para o desenvolvimento do carcinoma hepatocelular (CHC) e a exacerbação da hepatite aguda em indivíduos portadores do vírus da hepatite B (VHB). O uso de biomarcadores, como a aflatoxina M1 (AFM1) na urina, produto de biotransformação da aflatoxina B1 (AFB1), permite avaliar se a população está exposta às AFs. O objetivo do presente estudo foi investigar ocorrência de AFM1 na urina de portadores e não portadores crônicos do VHB. Foi selecionado um grupo, de forma aleatória, representado por 43 portadores do VHB atendidos em dois hospitais da cidade de Maringá, Brasil, no período de Março a Junho/2008. O grupo controle foi composto por 29 voluntários adultos saudáveis anti-HBs positivo e HBsAg negativo. A determinação de AFM1 foi realizada por meio de detecção por fluorescência em sistema de cromatografia a líquido de alta eficiência com derivação pós-coluna utilizando Kobra Cell®. Das 72 amostras analisadas, 05/29 (17,2%) foram positivas para AFM1 em indivíduos não portadores do VHB, e 16/43 (37,2%) de pacientes portadores do VHB. Este estudo demonstrou a ocorrência de AFM1 na urina dos dois grupos estudados. Entretanto, há evidências de que os portadores do VHB possuam alto risco no desenvolvimento do CHC devido ao efeito aditivo pela interação entre aflatoxinas e VHB.